Structure and Utilization of Receivable of Listed Non- Government Manufacturing Companies in Nepal - Gautam, Kedar Raj (Janapriya Journal of Interdisciplinary Studies, 2017)
When the firm sells goods on credit rather than requiring immediate cash payment such kind of credit sales generate accounts receivable. Especially in small firms, accounts receivable may be factor that decides success or failure. In large firms, efficient accounts receivable management affects the firm’s risk return and share price. The volume of receivable, their composition and management affects the liquidity and profitability. They have, therefore to be managed in such a way that strikes a balance between risk and return. This paper attempts to analyse the structure and utilization of receivable of listed manufacturing companies in Nepal. The emphasis in this study is on manufacturing enterprises because they provide best laboratory for analyzing the structure and utilization of receivable. To analyze the structure and utilization of receivable, ratio analysis is used along with statistical tools such as mean and standard deviation. The analysis shows that there was wide variation in investment in receivable. The average ratio of receivable to current asset ranged between 0.35% to 58%. Similarly, utilization of receivable in terms of average collection period ranged between 1 to 195.8 days representing on average 58.62 days. Janapriya Journal of Interdisciplinary Studies Vol. 2, No.1 (December 2013), Page: 65-72